Effects of injury and progesterone treatment on progesterone receptor and progesterone binding protein 25-Dx expression in the rat spinal cord - Labombarda, Maria Florencia (2003)
Progesterone provides neuroprotection after spinal cord injury, but the molecular mechanisms involved in this effect are not completely understood. In this work, expression of two binding proteins for progesterone was studied in intact and injured rat spinal cord: the classical intracellular progesterone receptor (PR) and 25-Dx, a recently discovered progesterone membrane binding site. RT-PCR was employed to determine their relative mRNA levels, whereas cellular localization and relative protein levels were investigated by immunocytochemistry. We observed that spinal cord PR mRNA was not up-regulated by estrogen in contrast to what is observed in many brain areas and in the uterus, but was abundant as it amounted to a third of that measured in the estradiol-stimulated uterus. In male rats with complete spinal cord transection, levels of PR mRNA were significantly decreased, while those of 25-Dx mRNA remained unchanged with respect to control animals. When spinal cord-injured animals received progesterone treatment during 72 h, PR mRNA levels were not affected and remained low, whereas 25-Dx mRNA levels were significantly increased. Immunostaining of PR showed its intracellular localization in both neurons and glial cells, whereas 25-Dx immunoreactivity was localized to cell membranes of dorsal horn and central canal neurons. As the two binding proteins for progesterone differ with respect to their response to lesion, their regulation by progesterone, their cellular and subcellular localizations, their functions may differ under normal and pathological conditions. These observations point to a novel and potentially important role of the progesterone binding protein 25-Dx after injury of the nervous system and suggest that the neuroprotective effects of progesterone may not necessarily be mediated by the classical progesterone receptor but may involve distinct membrane binding sites.